A comprehensive approach for calculating banking sector risks - Carmelo Salleo; Alberto Grassi; Constantinos Kyriakopoulos (International Journal of Financial Studies, 2020)
We propose a comprehensive approach for the analysis of real economy and government sector risk transmission to the banking system and apply it in ten Euro-Area countries from 2005 to 2017. A flexible methodology is developed to model banks' assets according to the risk-adjusted balance sheet of the counterparts. The use of distance to distress as a popular risk metric shows that Contingent Claims Analysis underestimates banks risk in stable periods and overstates it during crisis. Furthermore, the approach succeeds in detecting spillovers from households, non-financial corporations and sovereign sectors: for the countries examined the main source of instability comes from the Non-Financial Corporation sector and its increased assets volatility.
Keywords: G1; G2; G13; G32; G33; H63; 330; banking risks; distance-to-default; contingent claims analysis